The contribution of PISA to the convergence of education policies in Europe - Michel, Alain (European Journal of Education, 2017)
The international comparative studies on students’ outcomes have initiated analyses that have had a growing influence on national and sub-national education policies in industrialised and developing countries. It is particularly the case of the OECD's Programme for International Student Assessment (PISA) which started in 2000 and has organised surveys every 3 years, so that the 2015 survey was the 6th. Its influence has been particularly important for several reasons: 1) it assesses the basic competences in reading literacy, maths and science of 15 year-olds students, i.e. around the end of compulsory education in many countries; 2) the assessment is based on a reliable methodology and the tests are completed by qualitative surveys and studies; 3) and the results lead to recommendations and are amplified by the media in most countries. However, it is not easy to evaluate the real impact of PISA because of the existence of other international studies such as IEA's TIMSS and, particularly in Europe, the influence of the recommendations and benchmarks of the EU that has been growing steadily in the last 25 years. Our analysis of the impact of PISA and EU policy focuses on the evolution of the education policy in France, but also studies its evolution in a few other European countries. Finally, we underline the limits of the influence of PISA and international standards in education towards a convergence of education systems because of the importance of their specific historic and cultural contexts.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/ejed.12218
Keywords: European Commission; France; PISA; comparative indicators; education policy; student achievement